Analysis of the Pellet and Concentrate Chicken Animal Feed Production Process at PT. Japfa Comfeed Indonesia Gedangan Sidoarjo Unit: Analisis Proses Produksi Pakan Ternak Ayam Jenis Pellet dan Konsentrat di PT. Japfa Comfeed Indonesia Unit Gedangan Sidoarjo - Septyawan, Rio; Wulandari, Indah Apriliana Sari (Procedia of Engineering and Life Science, 2024)
This article reviews the production process of pellet and concentrate animal feed using the work mapmethod, both production process flow maps and production operation process maps. This research aims to carry outan analysis of the production process flow and find out the causes of any obstacles in the production process at PTJapfa Comfeed Indonesia Tbk Sidoarjo Unit, so that we can get a clear picture of the early stage process of producingpellet and concentrate animal feed. This type of research includes case study research because this research takes acompany as a case study, namely PT. Japfa Comfeed Indonesia, Tbk Gedangan Unit. The data collection method usesa field method, namely a data collection method that is carried out by conducting direct observations of the production process in the field, both by observation, interviews and documentation. The results are an analysis of the pellet and concentrate type animal feed production process at PT. Japfa Comfeed Indonesia Gedangan Sidoarjo Unit.